Wiley CPA examination review 1998 - Patrick R Delaney (John Wiley, 1998)
The book provides study outlines of Financial Accounting and Reporting: Business Enterprises. It includes a detailed solution guide for each accounting problem and outlines of the unofficial answers to essay questions published by the AICPA